Treatment patterns in a real-world cohort of patients with Wilson disease in the United States - Medici, Valentina; Kebede, Nehemiah; Stephens, Jennifer; Kunjappu, Mary; Vierling, John M. (Frontiers in Gastroenterology, 2024)
BackgroundWilson disease (WD) is a rare and potentially fatal genetic disorder caused by accumulation of toxic levels of copper. Current treatments include chelating agents and/or zinc. We characterized real-world US treatment patterns in patients with WD.MethodsThis retrospective, observational medical chart review utilized deidentified clinical data, including treatment patterns, abstracted from patient medical charts between 01/2012 and 06/2017. Line of therapy was assessed based on disease presentation and aggregated. Index treatment was defined as the first line of therapy, followed by second line of therapy and third line of therapy. Results were summarized using descriptive statistics.ResultsA total of 225 patients were included (mean [SD] age at diagnosis: 24.7 [9.8] years). Initial disease presentation was both neurologic/psychiatric and hepatic in 52.9%, followed by neurologic/psychiatric (20.0%), hepatic (16.9%), and asymptomatic (10.2%). Median (first and third quartiles) duration of follow-up from diagnosis was 39.5 (33.8–60.4) months. The most common first line of therapy was penicillamine monotherapy in 45.5%, followed by trientine monotherapy (26.1%) and chelator/zinc combination therapy (21.2%). A total of 167/222 (75.2%) patients remained on first line of therapy during the follow-up period. Of the 13.5% who switched to second line of therapy, most changed to trientine monotherapy (53.3%). All those who switched to third line of therapy transitioned to zinc monotherapy (100.0%). Unexpectedly, 11.3% discontinued first line of therapy without transitioning to a subsequent therapy. The primary rationale for index monotherapy selection was improved efficacy (61.6%). Most discontinuations were due to side effects/tolerability (40.8%). Treatment patterns varied by initial disease presentation, practice setting, physician specialty, and geographic location.ConclusionThese results demonstrate a lack of consensus in the US regarding first-line treatment for patients with WD. Evidence-based treatment pathways informed by high-quality clinical trials for improved health outcomes are needed.